The real life experience goes on: update after 4 years on the first cohort treated with lanadelumab at our center - Buttgereit, Thomas; Vera Ayala, Carolina; Aykanat, Seda; Weller, Karsten; Gutsche, Annika; Maurer, Marcus; Magerl, Markus (Frontiers in Immunology, 2024)
Introduction Lanadelumab is a first-line long-term prophylaxis (LTP) in hereditary angioedema (HAE). Real-life data on its long-term efficacy and safety are limited. It is unknown whether patients using lanadelumab need short-term prophylaxis (STP). Objective To provide 4-year follow-up data for our first 34 patients treating with lanadelumab. Methods Patients were assessed for their current injection interval, attacks, treatment satisfaction, disease control (AECT), quality of life impairment (AE-QoL), events that can induce attacks, and the use of STP since the start of their treatment with lanadelumab. Results Of 34 patients who started lanadelumab treatment, 32 were still using it after 4 years, with a median injection interval of 33 (range 14-90) days. HAE patients (n=28) reported longer intervals, i.e. 33 (14-90) days, than patients with angioedema due to acquired C1 inhibitor deficiency (n=4, 23 [14-31] days). With their current injection intervals, used for a mean duration of 29 ±17 months, patients reported a yearly attack rate of 0.3 ±0.1. More than 70% of patients were attack-free since starting their current injection interval. All patients reported well-controlled disease, i.e. ≥10 points in the AECT; 21 patients had complete control (16 points). AE-QoL scores improved further compared to our initial report, most prominently in the fears/shame domain (-6 points). Treatment satisfaction was very high. No angioedema occurred after 146 of 147 potentially attack-inducing medical procedures without STP. Conclusion Our results demonstrate the long-term efficacy and safety of lanadelumab in real-life and question the need for STP in patients who use effective LTP.